Early manifestation of spasticity after first stroke in the territory of the internal carotid artery: A prospective multicenter study - Dorňák, Tomáš; Justanova, Maria; Konvalinková, Romana; Mužík, Jan; Hoskovcová, Martina; Srp, Martin; Říha, Michal; Navrátilová, Daniela; Otruba, Pavel; Gál, Ota; Dušek, Ladislav; Jech, Robert; et al. (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2018)
AIMS: The main aim of this study was to provide an estimate of the incidence and prevalence of spasticity following stroke in the internal carotid artery territory for Regional Stroke Centers in the Czech Republic. A secondary goal was to identify predictors for the development of spasticity. METHODS: In a prospective cohort study, 256 consecutive patients with clinical signs of central paresis due to a first-ever stroke were examined in the acute stage. All patients had primary stroke of carotid origin and paresis of the upper and/or lower limb for longer than 7 days after stroke onset. All were examined between 7-10 days after the stroke. We evaluated the degree and pattern of paresis, spasticity using the Modified Ashworth scale and the Barthel Index, baseline characteristics and demographic data. RESULTS: Of 256 patients (157 males; mean age 69.9±12.4 years), 115 (44.9%) patients developed spasticity during the first 10 days after stroke onset. Eighty-three (32.5%) patients presented with mild neurological deficit (modified Rankin Scale 0 - 2) and 69 (27.0%) patients were bedridden. CONCLUSION: Spasticity was noted in 44.9% patients with neurological deficit due to first-ever stroke in the carotid territory in the first 10 days after stroke onset. Severe spasticity was rare.
Keywords: arteria carotis interna; svalová spasticita; lidé; Adult; Middle Aged; Muscle Spasticity; Risk Factors; prospektivní studie; Female; Carotid Artery, Internal; Prevalence; Stroke; Humans; Prospective Studies; cévní mozková příhoda; lidé středního věku; mužské pohlaví; multicentrické studie jako téma; prevalence; ženské pohlaví; Aged, 80 and over; senioři nad 80 let; Male; Aged; dospělí; Multicenter Studies as Topic; rizikové faktory; senioři